PENYAMPAIAN RASA TAKUT DALAM FILM HOROR QODRAT KARYA CHARLES GOZALI - Namira, S F; Ap Sinaga, Corry Novrica (Jurnal Psikotes, 2024)
The growth in popularity of horror films can be seen from the high number of horror films produced and their success at the box office. One example of a famous horror film is Qodrat, directed by Charles Gozali, which was released in October 2022. Qodrat is a horror genre film that combines action and religion with a duration of 102 minutes where Vino G. Bastian plays the main character in this film as a Qodrat chaplain. The aim of this research is to find out every scene that shows fear in the horror film Qodrat by Charles Gozali and to draw conclusions from the film about what are the signs and signifieds through semiotic analysis. This research uses a qualitative approach with Ferdinand de Saussure's semiotic analysis method. In this theory, semiotics is divided into two parts, namely the signifier and the signified. This research was carried out by observing signs in several scenes, including the scenes at minute 35:30 and minute 1:05:39 which contain fear in the film Qodrat. Observations were made by watching films via the application streaming platform and taking screen captures of scenes that were deemed to contain markers and signs. The results of this research show that from the two Hude theories and Aditya's theory, differences can be seen where Hude expresses fear that occurs in changes in behavior, whereas according to Aditya the cause of fear can occur because of fear related to places, for example fear of the dark (achluphobia).